Anti‐inflammatory effect of fermented brown rice and rice bran with Aspergillus oryzae on mice. Issue 1 (1st December 2020) - Umeyama, Lin; Kasahara, Shiori; Sugawara, Misa; Yokoyama, Satoru; Saiki, Ikuo; Hayakawa, Yoshihiro
Abstract: Aim: In this study, we examined the anti‐inflammatory effect of fermented brown rice and rice bran with Aspergillus oryzae (FBRA) on acute and chronic inflammation mouse models. Methods: As an acute inflammation model, we used a 12‐O‐tetradecanoylphorbol‐13‐acetate (TPA)‐induced ear edema model. As a chronic inflammation model, we used an imiquimod (IMQ)‐induced psoriasis model and ragweed pollen‐induced allergic rhinitis model. We also investigated the effect of FBRA on the expression of inflammatory mediators in skin biopsies from the imiquimod‐induced psoriasis model. Results: The mice fed the 10% FBRA‐containing diet showed lower‐level inflammation among the three different experimental models. In the IMQ‐induced psoriasis model, mRNA expressions of IL‐17A, IL‐1β and COX‐2 were significantly inhibited in the skin tissue of mice fed 10% FBRA diet. Conclusion: Our data suggest the potential benefit of FBRA as a functional food to prevent excessive inflammation.